Pengaruh FAS Terhadap Kuat Tekan Beton Dari Agregat Sungai Krasak - Aswadi, Lalu Samsul; Yuwana, Dwi Sat Agus (Civiliza Publishing, 2025)
Concrete construction is widely used by the community, for example, building construction, bridge construction, port construction, girder construction, and others that require determining the quality of concrete. The use of concrete for protected and unprotected areas differs. In general, the community uses concrete construction for road hardening and for building their homes. In general, when mixing concrete, the water used during mixing tends to be free, without important rules, making it easy to work. This will affect the quality or grade of concrete. The research on the effect of water-cement ratio (W/C) on the compressive strength of concrete from Krasak river aggregates, as the main material that is currently widely available in the Krasak River, Pabelan River, and Kali Putih River. In these places, sand with various sizes and split or crushed stone from various stone crusher companies are available. This research follows the Indonesian National Standard (SNI) on the Selection of Concrete Mixtures for Normal Concrete, Heavy Concrete, and Mass Concrete. The concrete mixing is done with a volume ratio of 1pc:2ps:2split with six variations of W/C, namely 0.37, 0.46, 0.55, 0.61, 0.64, and 0.73. The sand and split materials are tested according to SNI, namely the testing of fine aggregate and coarse aggregate materials. Mix design is performed based on the data of fine and coarse aggregates. The test objects are made by mixing materials such as cement, sand, gravel, and water. The mixing is carried out by testing the fresh concrete or slump and making cylindrical test objects and soaking them for 28 days. Then, the compressive strength of the concrete is tested. The compressive strength test results show that the W/C ratios of 0.37, 0.46, 0.55, 0.61, 0.64, and 0.73 with slump values of 0, 3, 5, 8, 14, and 18 cm produce compressive strengths of 9.90, 13.75, 14.62, 20.18, 13.50, and 6.97 kg/cm2, respectively. From the test results, it can be seen that the best W/C ratio is 0.61 with a compressive strength of 20.18 kg/cm2.